Increased fluctuation of sulfur alleviates cadmium toxicity and exacerbates the expansion of Spartina alterniflora in coastal wetlands. (1st January 2022) - Wu, Yueming; Leng, Zhanrui; Li, Jian; Jia, Hui; Yan, Chongling; Hong, Hualong; Wang, Qiang; Lu, Yanyan; Du, Daolin
Abstract: Evidence suggests that the invasion of Spartina alterniflora ( S. alterniflora ) poses potentially serious risks to the stability of coastal wetlands, an ecosystem that is extremely vulnerable to both biological and non-biological threats. However, the effects and mechanisms of sulfur (S) in mediating the growth and expansion of S. alterniflora are poorly understood, particularly when sediments are contaminated with cadmium (Cd). A 6-month greenhouse study was conducted to evaluate the mediating effect of S on Cd tolerance and growth of S. alterniflora . Treatments consisted of a factorial combination of three S rates (applied as Na2 SO4 ; 0, 500, 1000 mg kg −1 dry weight (DW), as S0, S500, and S1000 ) and four Cd rates (applied as CdCl2 ; 0, 1, 2, 4 mg kg −1 DW, as Cd0, Cd1, Cd2, and Cd4 ). Results showed that although the exogenous S supply obviously increased Cd accumulation in roots (up to 71.22 ± 6.43 mg kg −1 DW) due to the decrease of Fe concentration in iron plaque (down to 4.02 ± 1.18 mg g −1 DW), biomass reduction and oxidative stress in plant tissues were significantly alleviated. The addition of S significantly up-regulated the concentration of compounds related to Cd tolerance, including proline and glutathione. Therefore, the translocation of Cd was restricted, and plant growth was not impacted. The present study demonstrated that the exogenous sulfur supply could promote the growth of S. alterniflora and enhance its tolerance to Cd. Therefore, under the effects of S. alterniflora, the increased fluctuations of S pool caused by the release and deposition of S might further exacerbate S. alterniflora expansion in Cd contaminated coastal wetlands. Graphical abstract: Image 1 Highlights: S supply inhibited iron plaque formation and induced higher Cd accumulation in roots. S supply improved Cd chelation and detoxification. S supply enhanced the Cd tolerance of Spartina alterniflora. There is a synergy between the sediment S pool and the expansion of S. alterniflora.